Development of General Biology Learning E-Modules Based on Constructivism - Rukmana, Musma; Andre Watung, Fernando; Hasmiati, Hasmiati; Putri Agustina, Tika; Restutiningsih Putri Utami, Aisyiah (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2024)
Higher education must adapt its educational practices to ICT, which is now developed rapidly. There are many different approaches, and constructivism-based e-module development is an alternative. This research used the R&D method by adapting the ADDIE development model, which aimed to produce constructivism-based e-module products that meet the criteria of being valid, effective, and practical for use in the learning process. The e-module developed was validated using an expert validation questionnaire filled out by two expert validators, with a result of 4.32, which was included in the valid category. The effectiveness of the e-module was obtained by 100% of students achieving learning completeness scores and increasing learning outcomes based on a normalized gain analysis of 0.71 (high category). The results of the e-module practicality test showed positive student responses, where 86.67% of statements were included in the very strong category and 13.33% in the strong category. Based on the research results, it can be concluded that the constructivism-based general biology learning e-module developed is valid, practical, and effective.